Mechanisms linking multi-year La Niña with preceding strong El Niño - Tomoki Iwakiri (Nature Portfolio, 2021)
Abstract El Niño-Southern Oscillation (ENSO), characterized by anomalous sea surface temperature in the central-eastern equatorial Pacific, is a dominant interannual variability, impacting worldwide weather and socioeconomics. The ENSO cycle contains irregularity, in which La Niña often persists for more than two years, called “multi-year La Niña”. Observational records show that multi-year La Niña tends to accompany strong El Niño in the preceding year, but their physical linkage remains unclear. Here we show using reanalysis data that a strong El Niño excites atmospheric conditions that favor the generation of multi-year La Niña in subsequent years. Easterly wind anomalies along the northern off-equatorial Pacific during the decay phase of the strong El Niño are found crucial as they act to discharge ocean heat content (OHC) via an anomalous northward Ekman transport. The negative OHC anomaly is large enough to be restored by a single La Niña and, therefore, causes another La Niña to occur in the second year. Furthermore, analyses of the Coupled Model Intercomparison Project Phase 6 (CMIP6) climate models support the abovementioned mechanisms and indicate that the occurrence frequencies of multi-year La Niña and strong El Niño are highly correlated.